Cyberloafing and Job Burnout Among Educators : How Does Organizational Commitment Play A Role as A Moderating Variable? - Ali, Muhammad Yusuf; Mulyati, Heti; Sukmawati, Anggraini (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to analyze the effects of job burnout and cyberloafing on educator performance and the role of job burnout on cyberloafing, moderated by organizational commitment. This research employs a quantitative approach to validate hypotheses involving educators from the State University with Legal Entity Status in West Java, using a sample of 377 respondents and a questionnaire instrument adapted from various previous studies. Data was collected through questionnaires and analyzed using the Partial Least Square Equation Modeling (PLS-SEM) technique with SmartPLS software. The results indicate that job burnout has a significant positive effect on cyberloafing, suggesting that higher levels of job burnout correspond to an increased tendency for cyberloafing. Meanwhile, organizational commitment is an effective moderator in reducing the negative impact of job burnout on cyberloafing, which in turn helps improve employee performance. Thus, the study demonstrates that job burnout increases cyberloafing behaviour and decreases employee performance, yet organizational commitment can act as an effective moderator to mitigate these negative impacts. The implications of this research suggest that educational organizations can reduce the negative impact of burnout and cyberloafing on educator performance by promoting organizational commitment. This can contribute to creating a healthier and more productive work environment.